Gottagift: a mobile application for online gift delivery in Shah Alam / Noradila Mohd Rozali - Mohd Rozali, Noradila (2021)
In this modern era of technology, people have been offered two choices in doing their shopping. They can freely choose to shop online or offline which means going and buy the things they need in the physical stores. Due to the current pandemic of Covid-19, most people are more preferred to shop online as it eases them in many ways. The current method, of choosing a gift is by using the social media platform that required users to compare the price and spend more time in choosing the best gift they need as they have to jump from one platform to another platform of social media. Hence, a mobile application that focussed on gift delivery in Shah Alam called GottaGift was developed to provide people to purchase a gift online through a mobile application. GottaGift is a mobile commerce application that helps users and gift shop owners to sell and buy their products in efficient and effective ways. However, this mobile application does not provide users with a payment gateway. They need to make an online transfer and the receipt of a successful transaction as proof of payment. For users, they are no longer have to scroll social media to finally find a suitable gift for their loved one that is within their budget. On the seller side, they can use this platform to sell their products. This project is using the android platform. Mobile Application and Development Lifecycle (MADLC) is the methodology used in developing this project. In the future, this project is recommended to include the mobile payment gateway instead of online banking so that the purchase will be easier and hassle-free. In a conclusion, GottaGift is a mobile application that can help both user and gift shop owner in Shah Alam to make a gift purchase without the need to scrolling social media or go to the physical store and also let the gift shop owner sell their product in effective ways.